Evolution of West Pomerania Towards a Green Region - Izabela Bludnik; Paulina Dąbrosz-Drewnowska; Hanna Pondel (Studia Maritima)
West Pomerania has become known in recent years as a national leader in green economic transformation. The purpose of the article is to present the evolution that West Pomerania has undergone, from a region whose economic importance in the post-war period was based primarily on environmentally burdensome industry, to an area at the forefront of economic modernisation and implementation of the European Green Deal. The reason for the change in the direction of development after 1989 was, on the one hand, the deep economic crisis of the first years of political transition – characterised by a radical decline in industrial production, based on outdated and environmentally harmful solutions and, on the other hand, Poland’s accession and entry into the European Union and access to huge financial resources from subsequent programs and funds. In addition, the increase in environmental awareness, technological progress and the requirements of competitiveness of the market economy have led to increasing investment in economic transformation based on green ventures. The research used literature on the subject, industry publications, reports and studies, basic methods of descriptive statistics and analysis of development trends. As the analysis shows, due to its natural conditions and industry specialisation, the evolution of West Pomerania into an environmentally friendly area is based on investments in renewable energy sources (RES), with a particular focus on the wind power sector, including offshore. The development of RES is gradual but systemic, and this is confirmed by the use of increasing funds for this purpose, including from EU regional programs. Although progress toward decarbonisation and “greening” of the region faces some problems, it is hoped that they will be overcome. Indeed, local authorities stress that the transition to a climate-neutral economy is a priority for West Pomerania.